Comparative temporal transcriptome analyses of SARS-CoV-2 delta and omicron variants ex-vivo infection in cat lung explant culture - Panwar, Anuradha; Raut, Ashwin Ashok; Bhatia, Sandeep; Pateriya, Atul; Kumar, Amod; Sood, Richa; Saran, Suneela; Sehgal, Prakriti; Mohan, Arya J.; Zararia, Akash; Mishra, Anamika (Frontiers in Cellular and Infection Microbiology, 2025)
The rapid evolution of SARS-CoV-2 variants, have posed significant public health challenges due to their heightened transmissibility and varying clinical outcomes. While the impact of these variants in humans has been extensively studied, their effect on domestic animals has not been explored thoroughly. Given the close contact between humans and pets, combined with documented cases of virus transmission from humans to domestic animals and the potential for these animals to act as viral reservoirs, highlights the importance of understanding the molecular dynamics of SARS-CoV-2 infection in them. Consequently, there is an increasing demand for infection models that closely mimic viral behavior in animal tissues. In vivo infection of cats or any other non-laboratory animal species is extremely resource intensive, time consuming, require ABSL3 facilities, and animal ethical clearances which are not practically possible for the majority of researchers. In this scenario the ex vivo cultures model can be an excellent alternative. Therefore, in this study, we have utilized an ex vivo lung explant culture model derived from domestic cats to examine the host’s response to Delta and Omicron variants of SARS-CoV-2 in cat lung explant culture. Comprehensive transcriptomic profiling at multiple time points post-infection revealed significant disruptions in genes associated with cell adhesion, structural components, extracellular matrix (ECM) organization and regulation, secreted and growth factors, and immune responses. Our study revealed that the Delta variant triggered early activation of genes associated with tissue damage as early as 12 hours post-infection (hpi). By 24 hpi, both the Delta and Omicron variants showed significant activation of these genes, with the Delta variant linked to the activation of a larger number of tissue damage-related genes. Notably, we identified several hub genes, including MMP9, CCL5, MCP-1/CCL2, VWF, HGF, ANGPT1, CD34, CD68, SPP1, IGF1, CSF1, and VCL, involved in critical signaling pathways such as focal adhesion, PI3K-Akt signaling, and TNF signaling. These hub genes hold potential as valuable biomarkers. This study provides key insights into the pathogenesis of SARS-CoV-2 in cats and highlights the utility of ex vivo lung explant cultures as a platform for studying viral infections.